2020
DOI: 10.3389/fmicb.2020.00625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Energy Levels on Rumen Fermentation, Microbial Diversity, and Feed Efficiency of Yaks (Bos grunniens)

Abstract: The microbial community of the yak ( Bos grunniens ) rumen plays an important role in surviving the harsh Tibetan environment where seasonal dynamic changes in pasture cause nutrient supply imbalances, resulting in weight loss in yaks during the cold season. A better understanding of rumen microbiota under different feeding regimes is critical for exploiting the microbiota to enhance feed efficiency and growth performance. This study explored the impact of different dietary energy levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 56 publications
11
56
3
1
Order By: Relevance
“…A previous study reported that Firmicutes had an important role in the process of energy absorption (Ley et al, 2006). Additionally, Firmicutes are known to be involved in the degradation of oligosaccharides, starch, and cellulose (Ahmad et al, 2020). In the rumen of yaks, the research found that the relative abundance of Firmicutes in the feeding group was significantly increased as compared with the grazing group (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…A previous study reported that Firmicutes had an important role in the process of energy absorption (Ley et al, 2006). Additionally, Firmicutes are known to be involved in the degradation of oligosaccharides, starch, and cellulose (Ahmad et al, 2020). In the rumen of yaks, the research found that the relative abundance of Firmicutes in the feeding group was significantly increased as compared with the grazing group (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Notably, Hayashi et al [ 25 ] demonstrated that Dialister populations were positively correlated with hyposalivation, which could play an important function in changing the rumen buffering ability and fluid turnover. Erysipelotrichaceae_UCG_002 belongs to the family of Erysipelotrichaceae and was previously reported to be associated with VFA synthesis and energy generation [ 26 ]. The specific association of Erysipelotrichaceae_UCG_002 with VFA is still elusive, and thus requires an in-depth exploration in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Corn starch is less available for ruminal fermentation than barley grain and, hence, there is a need to conduct more extensive processing, such as steam-flaking instead of a simple grinding, to achieve higher availability of starch [ 1 , 12 ]. The main energy source for ruminants is SCFA that could be an indicator of the ruminal fermentation [ 32 ]. Therefore, the greater SCFA observed in BG diets, the higher the “whole body” efficiency towards greater gain and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Among individual SCFA the molar proportions of propionate and butyrate were increased in calves fed BG, and in contrast, acetate was in a lower range in this diet. Propionate and butyrate are two main ruminal volatile fatty acids that function as chemical stimuli for rumen development and they could potentially supply greater energy than acetate [ 32 ].…”
Section: Discussionmentioning
confidence: 99%